Reciprocal relationships among influenza experiences, perceptions, and behavior: Results from a national, longitudinal survey of United States adults. (March 2022) - Nowak, Sarah A.; Parker, Andrew M.; Gidengil, Courtney A.; Richardson, Andrea S.; Walsh, Matthew M.; Kennedy, David P.; Vardavas, Raffaele
Abstract: Objective: Our objective was to model the reciprocal relationships of perceived risk of contracting influenza with and without influenza vaccination, vaccination behavior, and reported influenza illness. Methods: We fit structural equation models to data from a longitudinal survey of adults in the United States collected through the RAND American Life Panel. Data come from fall and spring surveys fielded before and after each of 3 influenza seasons, 2016/2017, 2017/2018, and 2018/2019, for a total of 6 waves. Results: As expected, reported influenza experience was associated with increased perceived influenza risk in subsequent survey waves. Furthermore, perceived risk was associated with subsequent vaccination behavior, such that vaccination was more common for those with higher perceived unvaccinated influenza risk and lower perceived vaccinated influenza risk. Perhaps surprisingly, both elements of perceived risk were also associated with a greater likelihood of subsequent reported influenza illness. This malleability in illness reports may reflect uncertainty, as more respondents reported being sick but being unsure about whether they had influenza than reported certainty that they had influenza. Conclusions: Interventions that influence perceptions about past experience with influenza, including increased testing and informational campaigns about influenza symptoms, could have unanticipated impacts on perceptions of influenza vaccination and vaccination behavior. Highlights: Perceived risk of influenza without vaccination is associated with greater likelihood of vaccinating. Perceived risk of influenza with vaccination is associated with decreased likelihood of vaccinating. Experience with influenza is associated with higher future perceived risk of influenza. Higher perceived risk of influenza may be more associated with interpreting ambiguous symptoms as influenza.